2019
DOI: 10.1002/ajb2.1209
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that seed predators constrain pollinator‐mediated trait evolution in a tropical vine

Abstract: Premise of the Study Turnover in biotic communities across heterogeneous landscapes is expected to lead to variation in interactions among plants, their mutualists, and their antagonists. Across a fragmented landscape in northern Costa Rica, populations of the euphorb vine Dalechampia scandens vary widely in mating systems and associated blossom traits. Previous work suggested that populations are well adapted to the local reliability of pollination by apid and megachilid bees. We tested whether variation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…capensis was modified by herbivory: selection on floral traits did not differ between the reduced pollinator access treatment and the reduced pollinator access + increased herbivory treatment (Table ). This result is consistent with a recent meta‐analysis (Caruso et al., ), which found that manipulating biotic factors other than pollinators had a relatively small effect on selection on floral traits, but is not consistent with the prediction that the evolution of floral traits in response to pollinator declines will depend on interactions with herbivores (Opedal et al., ). However, our power to detect selection on floral traits was limited by the modest sample size within each treatment ( N = 27–29).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…capensis was modified by herbivory: selection on floral traits did not differ between the reduced pollinator access treatment and the reduced pollinator access + increased herbivory treatment (Table ). This result is consistent with a recent meta‐analysis (Caruso et al., ), which found that manipulating biotic factors other than pollinators had a relatively small effect on selection on floral traits, but is not consistent with the prediction that the evolution of floral traits in response to pollinator declines will depend on interactions with herbivores (Opedal et al., ). However, our power to detect selection on floral traits was limited by the modest sample size within each treatment ( N = 27–29).…”
Section: Discussionsupporting
confidence: 82%
“…The effect of pollinator declines on selection on floral traits may depend on biotic and abiotic environmental factors other than pollinators (Opedal et al., ). One such environmental factor is herbivory.…”
mentioning
confidence: 99%
“…Changes caused by herbivores would reduce nectar and pollen resources for floral visitors, decreasing the attractiveness to pollinators and thus their abundance, creating a negative feedback for the maintenance of pollinator fauna, and potentially decreasing outcrossing rates in animal‐pollinated plants. However, with our current data we cannot test whether the evolution of floral traits in response to changes in the abundance of interacting species (e.g., pollinators) depends on selective pressures generated by other interactors (e.g., herbivores) (Opedal et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…We observed bumblebee visitation to virgin C. latistipula flowers to investigate the relationship between body size and behavior of the bees and their impact on the pollination performance and plant reproductive fitness (see Opedal et al [2023] for the definitions and components of pollination performance and reproductive fitness). We selected 5–10 flower buds from each of the 30 individuals of C. latistipula and covered them with small tulle bags to prevent visits by bees and other insects.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate fruit and seed production (female reproductive fitness, according to Opedal et al, 2023) after bumblebee visits, we inspected the plants and flowers once a week for fruit. Once fruit development began, we enclosed the immature fruit in a small tulle bag, and after its maturation (when it became dark and rattled), we collected the fruits.…”
Section: Methodsmentioning
confidence: 99%